Innovations in Bio-Inspired Computing and Applications Proceedings of the 8th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2017) held in Marrakech, Morocco, December 11-13, 2017 - Abraham, Ajith; Haqiq, Abdelkrim; Muda, Azah Kamilah; Gandhi, Niketa; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book highlights recent research results in Bio-Inspired Computing and Applications. It presents 33 selected papers from the 8th International Conference on Innovations in Bio-Inspired Computing and Applications (IBICA 2017), which was held in Marrakesh, Morocco from December 11 to 13, 2017. A premier conference in the nature-inspired computing field, IBICA is intended to bring together the world's leading researchers and practitioners interested in advancing the state of the art in biologically inspired computing, allowing them to exchange notes on a broad range of disciplines. The book offers a valuable reference guide for all researchers, students and practitioners in the fields of Computer Science and Engineering.
Dynamic Parameter Adaptation Using Interval Type-2 Fuzzy Logic in Bio-inspired Optimization Methods -- Reducing Blackhole Effect in WSN -- Minimum Spanning Tree in Trapezoidal Fuzzy Neutrosophic Environment -- Differential Evolution Assisted MUD for MC-CDMA Systems Using Non-Orthogonal Spreading Codes -- Solving the Problem of Distribution of Fiscal Coupons by Using a Steady State Genetic Algorithm -- A Survey of Cross-Layer Design for Wireless Visual Sensor Networks -- An IPv6 Flow Label Based Approach for Mobile IPTV Quality of Service -- NWP Model Revisions Using Polynomial Similarity Solutions of the General Partial Differential Equation -- Energy Consumption and Cost Analysis for Data Centers with Workload Control -- A Stochastic Game Analysis of the Slotted ALOHA Mechanism Combined with ZigZag Decoding and Transmission Cost.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence